2019
DOI: 10.1186/s12884-019-2341-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency status and its related risk factors during early pregnancy: a cross-sectional study of pregnant Minangkabau women, Indonesia

Abstract: Background Vitamin D deficiency (VDD) is a common problem in reproductive-aged women and has become a major public health problem worldwide. The effect of VDD in pregnancy has been associated with several adverse pregnancy outcomes. This study aims to assess the serum levels of 25-hydroxyvitamin D (25(OH)D) in the first trimester and its associated factors (socio-demographics, pregnancy profiles, dietary intake, and maternal anthropometry measurements) for the determination of vitamin D deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 31 publications
4
57
0
10
Order By: Relevance
“…Recent studies showed that VDD is common in Indonesian women (Aji et al, 2019;Putri et al, 2019;Silvia et al, 2019b). Our previous study in healthy young Minangkabau women found that 97.5% of subjects had VDD (Silvia et al, 2019b).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies showed that VDD is common in Indonesian women (Aji et al, 2019;Putri et al, 2019;Silvia et al, 2019b). Our previous study in healthy young Minangkabau women found that 97.5% of subjects had VDD (Silvia et al, 2019b).…”
Section: Discussionmentioning
confidence: 88%
“…Skin pigmentation type was also assessed by observation (Sachdeva, 2009). Serum 25(OH)D level was measured by ELISA method by using 25(OH)D ELISA Kit (Can-VD-510) produced by Diagnostic Biochem Canada (DBC®) (Silvia et al, 2019b;Aji et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The serum samples were separated by centrifugation at 3500 rpm at 4°C for 10 min, then stored in aliquots at − 80°C. Serum 25(OH)D level was measured by enzyme-linked immunosorbent assay (ELISA) method by using 25(OH)D ELISA Kit (Can-VD-510) produced by Diagnostic Biochem Canada (DBC®) [9,27]. Vitamin D status in this study was defined using the cut-off points suggested by Grant & Holick where vitamin D levels categorized as deficient (< 50 nmol/L = < 20 ng/mL), insufficient (50-79 nmol/ L = 20-31 ng/mL) or sufficient (80-250 nmol/L = 32-100 ng/mL) [28].…”
Section: Serum 25(oh)d Analysismentioning
confidence: 99%
“…A study in Kenya, a tropical country, showed that 51% of women had insufficient (< 75 nmol/L), and 21% had deficient serum 25(OH)D level (< 50 nmol/L) [8]. With the high prevalence of VDD in women reported in sunny countries [8][9][10], VDD in pregnant women needs particular attention because of the potential unwanted birth outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This was a secondary data analysis from "Vitamin D Pregnant Mother (VDPM) study in West Sumatra". 2,3 The third trimester pregnant women were enrolled from the public health centers in West Sumatra Province from January to March 2018. Structured questionnaires were used to collect the data of demographic, socio-economic, anthropometry, and health history.…”
Section: Faculty Of Medicine Andalas University Padang 25172 West mentioning
confidence: 99%